57. An observational study assessing definitively diagnosed peripheral neuropathy and neuropathic pain in patients with multiple myeloma. Issue 1 (January 2015) - Biasiotta, A.; Truini, A.; Leone, C.; Federico, V.; La Cesa, S.; Russo, E.; Di Stefano, G.; Pepe, A.; Finsinger, P.; Labriola, R.; Piroso, S.; Cruccu, G.; et al.
<x xml:space="preserve">Abstract</x> Patients with multiple myeloma commonly suffer from peripheral neuropathy often accompanied by neuropathic pain. In this observational study we assessed prevalence rates and variables associated with these common complications related to multiple myeloma. We collected 255 consecutive patients with multiple myeloma. All patients underwent periodic neurological examination, the total neuropathy score, nerve conduction study, and the DN4 screening tool for detecting neuropathic pain. In 68% of the patients clinical examination and nerve conduction studies disclosed a predominantly sensory axonal distal symmetric peripheral neuropathy, unrelated to age, but associated with the duration of disease, medications and diabetes. In 25% of patients the DN4 disclosed neuropathic pain unrelated to the severity of peripheral neuropathy. Our detailed diagnostic information on prevalence rates and variables associated with peripheral neuropathy and neuropathic pain in patients with multiple myeloma should help clinical pain management thus improving their quality of life.